Implementasi Bakti Sosial Dan Edukasi Anti Bullying Di Panti Asuhan Farhan Farouq Batam - Caesar Eric Raditya; Anjani, Dina; Hakim, Faisal; Damara, Raka Deva; Rossyafitri, Tiara (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Bullying is an act of violence and intimidation to scare others. Bullying has a significant impact on someone's psychological and social development. If it continues to happen, victims can experience negative effects physically, mentally, and even in their way of thinking. Therefore, it is essential for the community, especially the authorities, to prevent and address bullying to make victims feel safe. there was a social service activity at the Farhan Farouq Orphanage in Batam, where an anti-bullying workshop was held. The purpose of this activity was to teach the children at the orphanage to be more proactive in preventing and dealing with bullying around them. As a result, the children started to feel brave enough to speak up about the bullying they experienced and received proper solutions. Additionally, they learned ways to protect themselves and their friends from bullying. It is hoped that through this activity, the children can grow up in a safer and more supportive environment, and develop strong self-confidence to face a future challenges.